KOMITMEN INDONESIA DALAM PARIS AGREEMENT BERDASARKAN UNDANG-UNDANG NOMOR 21 TAHUN 2014 TENTANG PANAS BUMI - Handi Herawan; Ahmad Redi (Fakultas Hukum Universitas Tarumanagara, 2021)
The adverse impact of climate change is a major threat to human life and the environment, therefore it is the duty of the State to protect its citizens. Indonesia is one of the countries that signed the Paris Agreement on 22 April 2016, The Paris Agreement is in the United Nations Framework Convention on Climate Change (UNFCCC) on greenhouse gas emission mitigation, adaptation, and finance in Paris in 2015. Indonesia's role in the Paris Agreement convention is committed to reducing greenhouse gas emissions by 29% under any effort or business as usual (BAU) by 2030 and can be increased to 41% with international cooperation. The binding power of the Paris Agreement convention is based on the principles of International Law Pacta sunt servanda. The legal basis for pacta sunt servanda is regulated in Article 26 of the 1969 Vienna Convention on the Law of Treaties, in Article 26 pacta sunt servanda means that every treaty in force is binding on the countries that are members of the treaty and must be implemented in good faith. Indonesia has laws and regulations for the formation or development of geothermal energy or environmentally friendly renewable energy related to the Paris Agreement convention, one of which is Law number 21 of 2014 concerning geothermal energy.